Nutritional and fermentative characteristics of Cameroon grass silage with Pelipita banana - López-Herrera, Michael (2017)
The objective of this research was to determine the nutritional and fermentative characteristics of Cameroon grass silage with replacement of immature Pelipita banana fruit (Musa ABB). The experiment was carried out between May and September of 2015, using a random and unrestricted design with four treatments and three substitution levels of fruit (15; 30, 45% w/w) and one control (0% fruit) with molasses (3% w/w). Each treatment had five replicates. The materials were harvested and minced in Upala, Costa Rica; the experimental part was developed in Montes de Oca, Costa Rica. The blends were stored for sixty days in 5 kg bags. Treatments that used immature fruit presented higher values of pH and ammonia nitrogen, than treatments that used molasses, treatments that used immature fruit also showed higher concentrations of non-fibrous carbohydrates and energy. Dry matter only increased in the treatment that had a 45% substitution. However, in all treatments where the fruit was used, the concentration of the fiber components and the digestibility of the neutral detergent fiber were reduced, due to an increase in lignin concentration. The ensiled materials had the potential to produce 1.50-1.70 kg milk/cow, when are consumed 5 kg fresh material (MV)/animal, and 4.40-5.20 kg milk/cow when consume 15 kg MV/animal, based on the requirement of net breastfeeding energy with a consumption rate three times higher than maintenance (3x).